A blind dynamic fingerprinting technique for sequential circuit intellectual property protection - Zhang, Li (2014)
Design fingerprinting is a means to trace the illegally redistributed intellectual property (IP) by creating a unique IP instance with a different signature for each user. Existing fingerprinting techniques for hardware IP protection focus on lowering the design effort to create a large number of different IP instances without paying much attention on the ease of fingerprint detection upon IP integration. This paper presents the first dynamic fingerprinting technique on sequential circuit IPs to enable both the owner and legal buyers of an IP embedded in a chip to be readily identified in the field. The proposed fingerprint is an oblivious ownership watermark independently endorsed by each user through a blind signature protocol. Thus, the authorship can also be proved through the detection of different user's fingerprints without the need to separately embed an identical IP owner's signature in all fingerprinted instances. The proposed technique is applicable to both application-specific integrated circuit and field-programmable gate array IPs. Our analyses show that the fingerprint is immune to collusion attack and can withstand all perceivable attacks, with a lower probability of removal than state-of-the-art FSM watermarking schemes. The probability of coincidence of a 32-bit fingerprint is in the order of 10-10 and up to 1035 32-bit fingerprinted instances can be generated for a small design of 100 flip-flops.